STUDY OF PEAK EXPIRATORY FLOW RATE AMONG VEGETABLE FARMERS USING PESTICIDES IN BOYOLALI DISTRICT, CENTRAL JAVA, INDONESIA - Manggala Sariputri; Ari Probandari; _ Hartono; Eti Poncorini Pamungkasari; Isna Qadrijati (Sanata Dharma University, 2020)
Pesticides exposure affects respiratory system. The study of peak expiratory flow rate (PEFR) as a parameter of lung function changes due to limited pesticide among farmers. This cross-sectional study aims to analyze factors affecting PEFR and formulate a model for predicting PEFR among 76 vegetable farmers using pesticides in Tlogolele Village, Boyolali Regency. Data were collected through questionnaire-based interview and clinical examination. PEFR test was conducted using a peak flow meter while cholinesterase level was investigated using Deutsche Gessellschaftfur Klinische Chemie method. The data were analyzed using unpaired T-test and Pearson test continued by multivariate regression models. The examination showed 75% of subjects had abnormal PEFR. Cholinesterase, body mass index, smoking habits, personal protective equipment usage, pesticide dosage, length of work per day, and last time of spraying did not show a significant correlation with PEFR. On the other hand, age, height, weight, frequency of spraying, and spraying duration showed a significant correlation with PEFR and a prediction equation for PEFR model was obtained as R2=0.268 (p0.001). The developed model will be useful for early detection of abnormal lung function.